The influence of protocol design on the identification of ventilatory thresholds and the attainment of peak physiological responses during synchronous arm crank ergometry in able-bodied participants - Kouwijzer, Ingrid (Eur J Appl Physiol, 2019)
PURPOSE: To examine the effects of stage duration on power output (PO), oxygen uptake (VO(2)), and heart rate (HR) at peak level and ventilatory thresholds during synchronous arm crank ergometry. METHODS: Nineteen healthy participants completed a ramp, 1-min stepwise, and 3-min stepwise graded arm crank exercise test. PO, VO(2,) and HR at the first and second ventilatory threshold (VT1, VT2) and peak level were compared among the protocols: a repeated measures analysis of variance was performed to test for systematic differences, while intraclass correlation coefficients (ICC) and Bland–Altman plots were calculated to determine relative and absolute agreement. RESULTS: Systematic differences among the protocols were found for PO at VT1, VT2, and peak level. At peak level, PO differed significantly among all protocols (ramp: 115 ± 37 W; 1-min stepwise: 108 ± 34 W; 3-min stepwise: 94 ± 31 W, p ≤ 0.01). No systematic differences for HR or VO(2) were found among the protocols. VT1 and VT2 were identified at 52% and 74% of VO(2)peak, respectively. The relative agreement among protocols varied (ICC 0.02–0.97), while absolute agreement was low with small-to-large systematic error and large random error. CONCLUSIONS: PO at VTs and peak level was significantly higher in short-stage protocols compared with the 3-min stepwise protocol, whereas HR and VO(2) showed no differences. Therefore, training zones based on PO determined in short-stage protocols might give an overestimation. Moreover, due to large random error in HR at VTs between the protocols, it is recommended that different protocols should not be used interchangeably within individuals.